A study of South African computer users' password usage habits and attitude towards password security - Friendman, Brandon (Rhodes University, Faculty of Science, Department of Computer Science, 2014)
The challenge of having to create and remember a secure password for each user account has become a problem for many computer users and can lead to bad password management practices. Simpler and less secure passwords are often selected and are regularly reused across multiple user accounts. Computer users within corporations and institutions are subject to password policies, policies which require users to create passwords of a specified length and composition and change passwords regularly. These policies often prevent users from reusing previous selected passwords. Security vendors and professionals have sought to improve or even replace password authentication. Technologies such as multi-factor authentication and single sign-on have been developed to complement or even replace password authentication. The objective of the study was to investigate the password habits of South African computer and internet users. The aim was to assess their attitudes toward password security, to determine whether password policies aâ†µect the manner in which they manage their passwords and to investigate their exposure to alternate authentication technologies. The results from the online survey demonstrated that password practices of the participants across their professional and personal contexts were generally insecure. Participants often used shorter, simpler and ultimately less secure passwords. Participants would try to memorise all of their passwords or reuse the same password on most of their accounts. Many participants had not received any security awareness training, and additional security technologies (such as multi-factor authentication or password managers) were seldom used or provided to them. The password policies encountered by the participants in their organisations did little towards encouraging the users to apply more secure password practices. Users lack the knowledge and understanding about password security as they had received little or no training pertaining to it.
Keywords: Computers -- Access control -- Passwords; Computer users -- Attitudes; Internet -- Access control; Internet -- Security measures; Internet -- Management; Data protection